Positioning of multicapacitors in a radial distribution network using new analytical methods - Ousseyni, Hassane; FIFATIN, François-Xavier; Oloulade, Arouna; MOUKENGUE IMANO, ADOLPHE; VIANOU, COKOU ANTOINE (My University, 2022)
This paper consisted of sizing and positioning multiple capacitors at multi-node in the Maradi HV distribution network in Niger by a new modern analytical method based on the calculation of a stability identification index (BVSI). From this study, it is observed that the positioning of the 2100 kVAr, 1050kV Ar, and 2100 kV Ar power capacitors at node 31, node 84 and node 105 respectively in the 123-bus network of Maradi contributed to reducing the losses of this network by 20.71 % with a minimum voltage of 0.9172 pu. However, despite this improvement, 31.70 % of the nodes still remained within the critical ranges, hence the need for other equipment to improve the performance of distribution networks. The traditional means of improving the technical performance of distribution networks by means of capacitors is nowadays insufficient to maintain the indicative parameters of the technical performance of distribution networks in emerging countries within the normative limits.
Keywords: Generic Algoritm (GA); Bus Voltage Stability Index (BVSI; Distribution Static Compensator (DSTATCOM); Radial Distribution System (RDS)